2017
DOI: 10.17509/ijal.v6i2.4915
|View full text |Cite
|
Sign up to set email alerts
|

Projecting Gender Identity Through Metadiscourse Marking: Investigating Writers’ Stance Taking in Written Discourse

Abstract: The present study aimed at investigating gender identity through the expression of interpersonal metadiscourse stance marking. The current study investigated male and female authors' pattern of stance markers utilization, focusing on totally 60 English and Persian articles, and English articles written by Persian speakers. Based on Xu and Longs' (2008) classification, five categories of stance markers (textual, epistemic, attitudinal, deontic and causation) were identified and the frequencies of their occurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Giles (2008) has noted that gender is an important aspect influencing communication strategies of people besides other factors such as ethnicity, occupational status, and age. As a result, many scholars had made gender issues as the area of investigations (Keeler, 1990, Kuipers, 1990Hassan, 2000;Mahmud, 2008;Amir, Abidin, Darus, & Ismail, 2012;Mellor & Fung, 2012;Koeser & Sczesny, 2014;Ali & Krish, 2016, Anshori, 2016Aziz, Jin, &Nordin, 2016, andSeyyedrezaie &Vahedi, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Giles (2008) has noted that gender is an important aspect influencing communication strategies of people besides other factors such as ethnicity, occupational status, and age. As a result, many scholars had made gender issues as the area of investigations (Keeler, 1990, Kuipers, 1990Hassan, 2000;Mahmud, 2008;Amir, Abidin, Darus, & Ismail, 2012;Mellor & Fung, 2012;Koeser & Sczesny, 2014;Ali & Krish, 2016, Anshori, 2016Aziz, Jin, &Nordin, 2016, andSeyyedrezaie &Vahedi, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, informal conversation can usually depict the different involvedness level of gender because of its 'interactional nature' (Argamon et al, 2003, p. 322). In English articles written by Persian speakers, female writers used the same pattern as their native counterparts, while male ones were affected mostly by their native language (Seyyedrezaie and Vahedi, 2017). In addition, Hosseini and Tammimy (2016) and Jasmani, et al (2011) found that verbs and pronouns may also provide distinctive gender-oriented information.…”
Section: Introductionmentioning
confidence: 93%
“…Mastering a foreign language is impossible without active communication, the form and effectiveness of which largely depend on the gender behavior of students. Kissau [14], and Seyyedrezaie & Vahedi [15] consider gender to be an important aspect of individual student differences; as a result, gender influences and is influenced by many other variables. Many researchers have been trying to reveal gender differences that affect learning styles and strategies.…”
Section: -Literature Reviewmentioning
confidence: 99%